The Making of Everyday Heroes: Women's Experiences With Transformation and Integration. (July 2019) - Ross, Susan L.
Heroes are not born heroic. They achieve prominence because they dare to enter into a voyage to become an entirely different human being: to transform. What happens to the hero on return? This is a qualitative investigation into the experience of integrating a transformative journey in the lives of seven women, 1 to 3 years after life-changing travel. The method used was cooperative inquiry, a heuristic approach involving cycles of action and reflection to construct knowledge based on shared lived experiences and group analysis. Coresearchers convened over a period of 13 months to examine the question, "What is our experience of integrating transformation?" Findings yielded an underlying pattern comprising nine phases: (1) displacement, (2) grief and denial, (3) disorientation, (4) dismemberment, (5) surrender and healing, (6) birth, (7) abundance and creativity, (8) power, and (9) integration. A major outcome identifies the integration of transformation as a feminine descent into one's underworld, delineating a feminine complement to the already well-documented hero's journey. One unexpected result shows that in combination, the journey's ascent (transformative peak experiences) cultivates one's masculine; the descent (integrative deep experiences) develops one's feminine. Together, these rounds form an upright figure eight, a wholly realized transformation.